Walsh, Daphne. New Perlican Photograph of a woman in front of logs during the winter. - Barrett, Terra
A photograph of Leah (Warren) Hobbs at Black Duck Siding standing in front of wooden logs. Snow and trees can be seen in the background. Above the photo says "Family Memories" and below the photo says "Mom." The photograph was printed by Kodak.